The Effect of Workplace Incivility on Psychological Well Being in Health Nurses With Emotional Exhaustion as a Mediator Variable - Tamara Dwi Astari; Rahmi Lubis; Patisina Patisina (Journal of Educational, Health and Community Psychology, 2024)
Nurses are health services provider professionals. The work demands have detrimental effects on nurses' physical and mental health, which risk their psychological well-being. The psychologically well nurses will provide high-quality care with implications for patient recovery. Interpersonal relationships with co-workers and superiors influence nurses' well-being. Poor treatment in the work environment (workplace incivility) can cause nurses to be psychologically unwell. However, we do not yet know how workplace incivility affects psychological well-being. This study aims to examine the effect of workplace incivility on nurses' psychological well-being through the mediation of emotional exhaustion. This explanatory quantitative study involved 270 health nurses at Hospital X Medan. We analyzed data using the Structural Equation Model (SEM) with the Smart-PLS program. Results indicated that emotional exhaustion mediated the effect of workplace incivility on nurses' psychological well-being. This study contributes to nurses' well-being intervention, which is influenced by workplace incivility and mediated by emotional exhaustion.